Characterization of Inpatient Moyamoya in the United States: 1988–2004 - Lee, Darrin J.; Liebeskind, David S. (Frontiers in Neurology, 2011)
Background and Purpose: Moyamoya disease has been classically described by the Asian experience, yet clinical aspects of moyamoya phenomena in the United States remain vastly undefined. The multifocal occlusive arterial disorder may be linked with numerous conditions; however, later stages of this syndrome share common vascular pathophysiology. This study is aimed at characterizing inpatient moyamoya cases in the United States over a broad time span. Methods: A comprehensive analysis of the Nationwide Inpatient Sample of the Healthcare Cost and Utilization Project (Releases 1-13, 1988-2004) based on ICD-9-CM code 437.5 was performed. Annual percentages and trends analyses were conducted for demographic variables, admission characteristics, co-morbidities, and procedures. Results: 2247 admissions of moyamoya cases were analyzed from a wide geographic distribution throughout the United States between 1988 and 2004. Age at admission varied considerably (mean 29.6 ± 18.5 years), affecting women more frequently than men (61.9%). Various racial groups were identified (35.4% White, 19.7% African American, 5.6% Hispanic, 8.3% Asian or Pacific Islander, 1.4% Native American). Admissions were typically emergent (38.8%) or urgent (18.7%), although elective admissions occurred (24.4%). Aside from moyamoya, sickle cell disease was diagnosed in 13.6%, ischemic stroke in 20.7%, intracerebral hemorrhage in 7.4%, TIA in 3.4%, and subarachnoid hemorrhage in 3.1%. Cerebral angiography was performed in 24.9% while extracranial-intracranial bypass was done in 8.4% of patients. Conclusions: Moyamoya in the United States is a heterogeneous condition affecting individuals of all ages across a diverse racial spectrum and wide geographic distribution. Further recognition of moyamoya syndrome may facilitate ongoing research and future therapeutic approaches.